2019
DOI: 10.1111/cge.13504
|View full text |Cite
|
Sign up to set email alerts
|

MRX93 syndrome (BRWD3 gene): five new patients with novel mutations

Abstract: Overgrowth syndromes (OGS) comprise a heterogeneous group of disorders whose main characteristic is that either the weight, height, or head circumference are above the 97th centile or 2 to 3 SD above the mean for age and sex. Additional features, such as facial dysmorphism, developmental delay or intellectual disability (ID), congenital anomalies, neurological problems and an increased risk of neoplasia are usually associated with OGS. Genetic analysis in patients with overlapping clinical features is essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…It is over a decade since BRWD3 disruption was first shown to cause an intellectual disability syndrome in males (Field et al, 2007). However, with only three clinical reports, we know surprisingly little about the BRWD3 phenotype (Field et al, 2007; F o r P e e r R e v i e w Grotto et al, 2014;Tenorio et al, 2019 Relatively little is known about the biology of the BRWD3 phenotype, and to our knowledge, there have been no reports of knockout models or functional studies in mammalian models. However, a possible mechanism of pathogenesis of the OGID phenotype is suggested by experiments in Drosophila, which found that loss of the BRWD3 homologue leads to increased histone H3.3 levels and wide-ranging effects on gene transcription mediated through histone-dependent chromatin regulation (Chen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is over a decade since BRWD3 disruption was first shown to cause an intellectual disability syndrome in males (Field et al, 2007). However, with only three clinical reports, we know surprisingly little about the BRWD3 phenotype (Field et al, 2007; F o r P e e r R e v i e w Grotto et al, 2014;Tenorio et al, 2019 Relatively little is known about the biology of the BRWD3 phenotype, and to our knowledge, there have been no reports of knockout models or functional studies in mammalian models. However, a possible mechanism of pathogenesis of the OGID phenotype is suggested by experiments in Drosophila, which found that loss of the BRWD3 homologue leads to increased histone H3.3 levels and wide-ranging effects on gene transcription mediated through histone-dependent chromatin regulation (Chen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…An in‐house bioinformatic pipeline was developed to analyze the raw data. This pipeline consists of base calling, alignment, local realignment, duplicate removal, quality recalibration, data merging, variant detection, genotyping and annotation was described in previous reports . In parallel to analysis process, an exhaustive quality control of the sequenced samples was performed according a custom pipeline .…”
Section: Methodsmentioning
confidence: 99%
“…This pipeline consists of base calling, alignment, local realignment, duplicate removal, quality recalibration, data merging, variant detection, genotyping and annotation was described in previous reports . In parallel to analysis process, an exhaustive quality control of the sequenced samples was performed according a custom pipeline . Review, classification and interpretation of the variants were made according to the American College of Medical Genetics and Genomics (ACMG) guidelines …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant dBRWD3 (also named as ramshackle in Drosophila) leads to dying earlier during the development [8,9] or to disrupt dendritic morphogenesis and sensory organ differentiation [10]. In human, abnormal BRWD3 expression causes intellectual disability [11][12][13][14][15][16][17][18][19], leukemia [20], breast cancer [21] and head & neck cancer [22]. The human BRWD3 containing several WD repeats and 2 bromodomain (BRD) repeats, belongs to bromodomain-contain proteins (BCPs) family [12].…”
Section: Brwd3 (Bromodomain and Wd Repeat Domain Containing 3)mentioning
confidence: 99%